Heliconia Society Cultivar Registration - Skinner, Dave; Hintze, Jan; Brunner, Bryan (Journal of Tropical Crop Science, 2014)
The Heliconia Society International (HSI, website: www.heliconia.org) is a non-prot corporation formed in 1985 because of rapidly developing interest around the world in these plants and their close relatives.The purpose of HSI is to increase the enjoyment and understanding of Heliconia and related plants (in the families Cannaceae, Costaceae, Lowiaceae, Marantaceae, Strelitziaceae, and Zingiberaceae) of the order Zingiberales through education, research and communication. Interest in Zingiberales and information on the cultivation and botany of these plants is rapidly increasing. HSI will centralize this information and distribute it to members.